ChemInform Abstract: Rhodium(III)‐Catalyzed Dehydrogenative Heck Reaction of Salicylaldehydes. Issue 5 (13th February 2013) - Shi, Zhuangzhi; Schroeder, Nils; Glorius, Frank
Abstract The title reaction complements the Heck reaction on carbonyl substrates and provides substrates like aurones, e.g. (III), flavone (XVI), flavanone (XVII), and 2′‐hydroxychalcones, e.g. (XIV), from readily available starting materials.